ЖАНРОВО-СТИЛЕВОЕ ОБНОВЛЕНИЕ РОМАНА (Scientific journal of the Fergana State University, 2023)
This article discusses the formation of the Uzbek novel, also the peculiarities of the romance philology of the period of Independence.